A psychological approach to Model Iranian Demand for Internet - Amin Kouhbor, Mohammad; Ghasemi Varnamkhasti, Ebrahim; Yousefi, Homayoun (International Journal of Psychosocial Rehabilitation, 2021)
This article is aimed to identify the factors affecting demand for internet use among Iranian people with a special consideration of its psychological foundation. For this reason, we used Iran's Income expenditure survey data in 2019, Households internet expenditure as dependent, and some Economic, Geographic and demographic variables as control variables. Based on Double hurdle estimations, the expenditure on home internet is governed by two decisions, the decision to participate in internet connection and the decision on the amount of data to be used. Also, these two decisions, could determine by two separate sets of variables. Some household characteristics such as age, number of under 8 years members in a household, education and the economic variables found to be significant in both decisions, while the geographic ones, were only significant in the participation equation.